(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article presents the pedagogical conditions for forming a scientific worldview of future teachers through independent thinking, its scientific substantiation, the use of interactive educational technologies in the educational process and some considerations on the formation of a scientific worldview on this basis.